EVALUATION OF SOME ACTIONS OF THE RURAL RENEWAL PROGRAM CARRIED OUTFOR THE PURPOSE OF SUSTAINABLE AGRICULTURAL DEVELOPMENT - CASE OF THE MUNICIPALITY OF ZEBOUDJA (THE PREFECTURE OF CHLEF, ALGERIA) (International Journal of Innovative Technologies in Economy, 2024)
In order to ensure sustainable agricultural development in the country, food security for the population, and thus minimize imports, the Algerian government has since 2008 adopted a new strategy for agricultural renewal. This is called “rural renewal”, and its main objective is to improve the living conditions of the population, to slow down rural exodus, and thus prevent the abandonment of agricultural land.This new strategy has been implemented since 2009 through Integrated Rural Development Proximity Projects (IRDPP), particularly in poor and marginalized areas. After more than a decade since the launch of these projects at the national level, we deemed it useful to conduct an evaluation of the status of the actions carried out and their impact on the population and the rural environment in the Municipality of Zeboudja (the Prefecture of Chlef). To do this, data collection was carried out at the level of specialized administrations and field visits were conducted. The results obtained show a certain improvement in the living conditions of the population, particularly at the infrastructure level (access roads for isolation and mobilization of water). Collective and individual actions have shown a satisfactory success rate.